Promotion of Central Java Tourism via the Central Java Disporapar Instagram Account - Rahmaditya, Ray Riza Ghani; Zulfiningrum, Rahmawati (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Central Java has a variety of interesting tourism destinations for tourists to visit. Central Java Disporapar carries out tourism promotions by utilizing Instagram media as a promotional tool. This research uses the theory of Technological Determination which focuses on: 1) Changes in Human Technology, 2) Changes in Various Communications, 3) The Emergence of Communication Equipment by Humans. Supported by the 7P Promotion Mix theory (Promotion Mix), namely 1) Service Provider. 2) Process. 3) Physical Support Facilities. 4) Products. 5) Price. 6) Distribution Channels. 7) Promotion. This research uses qualitative methods and a netnographic approach through online data collection techniques through observing followers such as likes, comments and shares as well as the interaction of the Disporapar Jateng Instagram admin with followers, content analysis to identify the type of content, visual style and message delivery of each post. Data collection was also carried out through in-depth interviews and documentation. The results of research on Technological Determination in Central Java Disporapar: 1) Changes in Human Technology, Updating devices for content production on Instagram, 2) Changes in Various Communications, Promotion of Central Java tourist destinations carried out online via Instagram media, 3) The emergence of Human Communication Equipment, Websites " visitjawatengah.jatengprov.go.id” as a new breakthrough in Central Java information. Through the 7P Promotion Mix (Promotion Mix), dividing elements from the Public Relations and Marketing workforce to cover Central Java tourist destinations for marketing. Financial operational costs are regulated in the context of content production, human resources and other needs. The product is in the form of Instagram feed content containing the city of Central Java and the uniqueness of the city such as tourism destinations and typical culinary delights. Through Technological Determination, the use of technology in communication on Instagram media by the Central Java Disporapar to reach a wider audience and the implementation of the 7P Promotional Mix so that the implementation of promotions is in accordance with the seven elements of the promotional mix.